Software Methodology for Data Control and Collection for Autonomous Monitoring Systems with a Large Amount of Generated Information on the Example of Software for a Hydrological Radiolocation System - I. S. Serdiukov; V. I. Veremyev; Van Tuan Nguyen (Известия высших учебных заведений России: Радиоэлектроника, 2023)
Introduction. The current data monitoring and collection systems produce a growing amount of generated information. Such factors, as the increasing sampling rate of ADCs and the increasing speed of systems for primary processing, receiving, and transmitting information, etc., make the systems operate almost at the bandwidth limit of data transmission interfaces. In some applications, such a flow is redundant and can be optimized through the use of various algorithms for the primary processing of information. However, in some applications, reducing the data flow is impossible, since the received information is processed with a delay. Therefore, the development of a software methodology for controlling and collecting data in the system of automatic monitoring of the sea surface by a hydrological radiolocation system seems a relevant research task.Aim. To synthesize a methodology and to develop software for controlling the information system of radar monitoring of the sea surface.Materials and methods. System approach, software architectural and algorithmic design, software quality management methods, system analysis, Qt framework, C++ programming language.Results. A working methodology for designing software for controlling information and measurement technologies with a large amount of generated data was obtained. The effectiveness of the methodology and software quality were confirmed by control tests. A 3-month autonomous testing of the stability and reliability of the system was carried out. Detection of data loss in the system comprised less than 0.002 %, thus not exceeding the specified critical level of 0.5 %.Conclusion. The developed methodology can be used in designing software for controlling information and measuring systems generating a large amount of data. The approaches used to build a multithread software architecture with asynchronous data flow control has shown their high efficiency.